Effect of Aging on Tympanometric Findings in Indian Population - Sinha, Sujeet Kumar; Neupane, Anuj Kumar; Gururaj, Krithika (Annals of Otology and Neurotology, 2021)
Introduction Presbycusis, or age-related hearing loss being a cumulative effect of aging on hearing, is a progressive and irreversible bilateral symmetrical sensorineural loss. In older individuals, one of the most important structures which undergo changes due to aging is the middle ear. There is a dearth of studies in Indian population regarding the tympanometric characteristics in older individuals. Thus, this study was taken up with an objective to report the different tympanometric characteristics in elderly individuals (aged above 50 years) who reported with ear- or hearing-related complaints to the Department of Audiology, All India Institute of Speech and Hearing, Mysore, Karnataka, India.Materials and Methods A register-based analysis was conducted where immittance tests were performed.Results There was no effect of age on static admittance, ear canal volume, and tympanometric peak pressure values. Also, there was no gender effect on tympanometric findings.Conclusion The result of the present study helps in understanding the different middle ear mechanisms in older adults.
Keywords: presbycusis; tympanometric width; ear canal volume; static admittance